Assessment of the biofilm formation capacities of Staphylococcus aureus strains Newman and Newman D2C in vitro and in vivo - Ben Wieland; Gubesh Gunaratnam; Linda Pätzold; Noran Abdel Wadood; Georges Pierre Schmartz; Swarnali Kundu; Nikolay Krasimirov Kirilov; Ina Krüger; Mohamed Ibrahem Elhawy; Jacqueline Rehner; Hannah Heintz; Frank Schmitz; et al. (Scientific Reports)
Abstract Staphylococcus aureus is a major cause of implant-associated infections (IAIs). The ability of this Gram-positive bacterium to cause IAIs is closely related to its capacity to attach to and to form biofilms on the implant material. Biofilm formation of S. aureus on artificial surfaces is usually mimicked in the laboratory by simple microplate-based in vitro assays and often involves type culture collection preserved laboratory strains such as SA113 (ATCC 35556), Newman (NCTC 8178), and Newman D2C (NCTC 10833, ATCC 25904). The latter two strains are phylogenetically closely related and often inadvertently indicated as strain “Newman” in publications, albeit of the fact that strain Newman D2C harbors among others mutations in the global regulatory loci agr and sae, which strongly impact the phenotypic behavior of this strain. Wondering how the genetic differences between strains Newman and Newman D2C alter the biofilm formation capacities of these two strains in vitro and in vivo, we tested here the adhesion behavior and biofilm formation capacities of both strains on different kinds of artificial surfaces (tissue culture-treated bottoms of 96-well polystyrene microplates and polyurethane-based peripheral venous catheter [PVC] tubing). Additionally, we determined their ability to cause infection in a foreign body-related murine infection model. Our studies revealed that the Newman and Newman D2C derivatives kept at Saarland University, Germany, differ significantly in their abilities to attach to microplate well bottoms and PVC tubing, and to form biofilms in various static and dynamic in vitro assays. However, when the biofilm formation capacities of both strains were determined in an in vivo infection model, rather comparable bacterial loads were observed. These findings suggest that biofilm formation capacities of S. aureus strains may differ substantially in vitro and in vivo. Additionally, researchers working with strains Newman and Newman D2C should be aware that both strains differ substantially in their phenotypic behavior, and that both strains should be indicated correctly to allow for a better comparison of data obtained with these strains in different laboratories.